ANALYSIS OF RICE PROCESSING IN YOBE STATE, NIGERIA - Lawal, A. A.; Ibrahim, H.I.; Adeola, S.S.; Lawal A.T. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study analyzed rice processing in Yobe State, Nigeria. A multistage sampling technique was used in selecting 70 respondents from the study area. Data were collected through the administration of structured questionnaires and interviews. Various analytical tools were employed, including descriptive statistics, Net Farm Income and market efficiency indices. Findings revealed balanced gender distribution among the respondents, with 41% female participation. The results also revealed that 42.9% of the respondents were single with only few having formal education. Almost half (48%) of the respondents fall within the age group of 31-40. Economically, rice processing in the study area was profitable, on average, processors earn a net income of ₦9632 per 75kg bag with a return of 34% per naira and marketing efficiency of 116%. Processors struggle with multiple taxation (55.71%), unreliable electricity (50%), and inconsistent raw material supply (42.86%). The study concludes that rice processing in Yobe state is profitable and based on the constraints highlighted the study recommended that there should be deliberate efforts by government and private investors to provide modern processing equipment for the local rice industries to enhance the efficiency, equity, and sustainability of rice processing in Yobe State. These investments are expected to improve the quality of Nigerian local rice, ultimately boosting its competitiveness among the various rice options consumed by households in Nigeria.